2016
DOI: 10.1007/s10461-016-1449-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Sexual Risk of HIV Transmission Among HIV-Positive Latino Men Who have Sex with Men on the U.S.-México Border

Abstract: We present results from a cross-sectional, clinic-based survey of border-region Latino men who have sex with men (MSM) and who also are living with HIV in the El Paso-Ciudad Juárez area. Among the 66 participants who reported serodiscordant anal or vaginal intercourse, we examined levels of psychological distress and substance use and the association of these variables with condomless sex. Bivariate analyses indicated that MSM who reported condomless sex with a serodiscordant partner were more likely to report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…In a study in Iran, residents living in the border area reported that their knowledge mainly came from their individual experiences instead of health promotion programs [19]. Collectively, they pose a preferable condition for the escalation of HIV/AIDS epidemic, raising urgent needs of interventions to promote HIV-related KAP in order to prevent and reduce risk behaviors among residents in border zones [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…In a study in Iran, residents living in the border area reported that their knowledge mainly came from their individual experiences instead of health promotion programs [19]. Collectively, they pose a preferable condition for the escalation of HIV/AIDS epidemic, raising urgent needs of interventions to promote HIV-related KAP in order to prevent and reduce risk behaviors among residents in border zones [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Economic disruption, psychological stress, population mobility and displacement, trauma and physical violence, and military activity associated with migration are risk factors for HIV transmission [15,16]. Untreated substance use and mental health problems can affect the perceived risk for HIV acquisition and promote high-risk behaviors such as sexual concurrency, unprotected anal intercourse, and injection drug use (IDU) [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…While much research has focused on depression as a predictor of HIV risk and treatment outcomes (23,25,42), less research has focused on anxiety or trauma-related disorders as distinct from depression in the context of condomless sex (43,44). The few extant studies that have done so did not include women and did not highlight unstable housing (43,(45)(46)(47). Our findings show only slightly attenuated independent associations with panic attack or PTSD in the presence of sex exchange.…”
Section: Discussionmentioning
confidence: 55%